CVD-graphene/graphene flakes dual-films as advanced DSSC counter electrodes. (9th April 2019) - Capasso, Andrea; Bellani, Sebastiano; Palma, Alessandro Lorenzo; Najafi, Leyla; Del Rio Castillo, Antonio Esaù; Curreli, Nicola; Cinà, Lucio; Miseikis, Vaidotas; Coletti, Camilla; Calogero, Giuseppe; Pellegrini, Vittorio; Di Carlo, Aldo; et al.
Abstract: The use of graphene-based electrodes is burgeoning in a wide range of applications, including solar cells, light emitting diodes, touch screens, field-effect transistors, photodetectors, sensors and energy storage systems. The success of such electrodes strongly depends on the implementation of effective production and processing methods for graphene. In this work, we take advantage of two different graphene production methods to design an advanced, conductive oxide- and platinum-free, graphene-based counter electrode for dye-sensitized solar cells (DSSCs). In particular, we exploit the combination of a graphene film, produced by chemical vapor deposition (CVD) (CVD-graphene), with few-layer graphene (FLG) flakes, produced by liquid phase exfoliation. The CVD-graphene is used as charge collector, while the FLG flakes, deposited atop by spray coating, act as catalyst for the reduction of the electrolyte redox couple (i.e. - and Co +2/+3 ). The as-produced counter electrodes are tested in both - and Co +2/+3 -based semitransparent DSSCs, showing power conversion efficiencies of 2.1% and 5.09%, respectively, under 1 SUN illumination. At 0.1 SUN, Co +2/+3 -based DSSCs achieve a power conversion efficiency as high as 6.87%. Our results demonstrate that the electrical, optical, chemical and catalytic properties of graphene-based dual films, designed by combining CVD-graphene and FLG flakes, are effective alternatives to FTO/Pt counter electrodes for DSSCs for both outdoor and indoor applications.